Typical linguistic errors committed by tertiary students in legal written outputs - Ai Nhan Nguyen; Tuan Van Vu (East European Journal of Psycholinguistics)
Legal English writing, which demands precision, formal tone, and adherence to specific conventions, presents significant challenges for English as a Foreign Language (EFL) learners due to the complexity of syntax, specialized legal vocabulary, and rigid grammatical structures. This research examines how these morphological, lexical, syntactic, and mechanical errors impact writing performance and explores the relationship between the frequency of errors and overall writing proficiency. Conducted at Hanoi Law University, Vietnam, the study followed 57 students majoring in legal English through three assessment phases: Pre-Test, Post-Test no.1, and Post-Test no.2. The research utilized a longitudinal quantitative design, analyzing the evolution of participants’ writing over time and evaluating common grammatical errors they faced. Results showed notable improvements in both morphological and lexical accuracy, evidenced by a reduction in error rates and greater consistency in participants’ performance. The proportion of respondents achieving higher proficiency levels (Intermediate and Upper-Intermediate) increased significantly, particularly in morphological and lexical domains. However, syntactic errors exhibited more complex patterns, with some improvements but continued challenges, suggesting that syntactic accuracy requires more focused and specialized intervention strategies. Mechanical errors remained relatively stable, with slight fluctuations, reflecting a steady performance in this area. Overall, the findings highlight the effectiveness of targeted instructional strategies in enhancing learners’ linguistic accuracy, particularly in morphological and lexical errors, while underscoring the need for teachers’ tailored interventions to improve students’ syntactic competence in legal English writing skills.